Transformasi Fungsi Peta dalam Pembelajaran Sejarah: Penguatan Analisis Historis dan Wawasan Lingkungan bagi Siswa - Qonita Fadhila; Suryo Ediyono (Historia Pedagogia, 2026)
This article aims to: 1) examine the transformation of the map function from visual media to a historical analysis instrument, 2) examine the strategy of map implementation as an instrument of historical analysis based on the relationship between human and environment, and 3) examine the pedagogical implications of the implementation of the map function transformation in history learning. This article uses the literature review research method, which involves reading, understanding, studying, synthesizing, summarizing, comparing research results, and creating literature reviews from previous research. The results of the study in this article are: 1) the transformation of the map function as an instrument of historical analysis is able to integrate the spatial dimension as an integral part of historical analysis, 2) the strategy of implementing the map function as an instrument of historical analysis as well as the integration of environmental knowledge can be carried out by the analysis of the kingdom territory, the analysis of spice paths, and the application of problem-based learning, and 3) the pedagogical implications are shifting the roles of teachers and learners, the development of contextual learning, and reinforcement relevant to 21st century learning.